Pengembangan Media Boneka Flanel Untuk Meningkatkan Minat Belajar Dongeng Pada Siswa Kelas IV SD Negeri 105370 Petuaran Hilir - Melati Senja Cahaya, Shabrina Anshor (Ability: Journal of Education and Social Analysis, 2022)
The objective of this research was to investigate students’ fairy tale learning interests through “flannel dolls” media by grade IV students of SD Negeri 105370 Petuaran Hilir. The development model or Research and Development (R&D) conducted in this research was to use a 4-D development model because the existing stages were clear and explained briefly the development process. This research instrument was in the form of validation sheets from material experts and media experts. Data collection tools were used in accordance with validity and reliability or consistency to obtain data as a burden in research using questionnaires to obtain data about the feasibility of product. This medium was validated by material experts and media experts. After being validated by material experts and media experts, the media was then revised so that the media revision phase I got. Media results of stage I revision were then piloted by means of use by teachers in classroom learning. Media that had gone through the trial process would be revised again. Based on these stages, it would be produced the final product “Development of Flannel Doll Media to Increase Interest in Learning Fairy Tales.” Through the results of media expert validation, it is known that 19 of 20 questions stated “YES” and 1 question stated “NO” as the assessment category. It is suggested that media experts state that flannel doll media was WORTHY to be studied and used as a medium of learning Bahasa Indonesia on fairy tale material and concluded that flannel doll media in Bahasa Indonesia learning developed experienced excellent quality development and worthy of trial. This can be proven by the assessment obtained from the initial product did not experience improvements in the product developed.